The effects of sevoflurane and halothane anesthesia on bupivacaine cardiotoxicity in rabbits [Tavsanlarda halotan ve sevofluran anestezisinin bupivakain kardiyotoksisitesi uzerine etkileri] - (:unkn) unknown (My University, 1998)
This study is performed in 20 adult rabbits weighing 1972 ± 381.9 gm.s in order to compare the effects of halothane and sevoflurane anesthesia on bupivacaine cardiotoxicity. The rabbits randomly assigned to either or halothane and sevoflurane group (n=10). Without any premedication, after mask induction with these agents they were endotracheally intubated. The rabbits were paralysed with 0.1 mg/kg vecuronium bromide intravenously, and were ventilated mechanically with 70 % nitrousoxide, 30 % oxygen, 1 % halothane in group 1 and 70 % nitrousoxide, 30 % oxygen, 2 % sevoflurane in group 2 for 15 minutes. By this time, 2 mg/kg 0,5 % plain bupivacaine infusion was started. When any arrythmias were was observed, the rabbits were ressuscitated with a predetermined protocol and the total dose of bupivacaine causing arrythmia, the time to cardiac depression, the duration of ressuscitation, mean arterial pressure, the heart rate, the blood gas and electrolyte values before and after the occurrence of the arrythmia were recorded and compared statistically. Although the cardiac toxicity was observed earlier and with a lesser dose of bupivacaine in the halothane group than in the sevoflurane group, the difference was not significant statistically. The duration of the ressuscitation was longer in rabbits in the sevoflurane group. All rabbits were recovered without any complication. We concluded that while performing regional block with bupivacaine under general anesthesia, sevoflurane should be preferred to halothane.
Keywords: Bupivacaine; Cardiotoxicity; Complications; Halothane; Inhalational anesthetics; Local anesthetics; Sevoflurane